Gender gap in mental health research productivity: Results from Qatar - Dalia Albahari (17115664) (2020)
Objectives Qatar’s contribution to biomedical research has increased significantly in the past couple of decades, but the exact participation of women researchers remains obscure. This study aims to explore the gender gap in research production of Qatar in the field of mental health. Methods The authors searched five databases for published articles from Qatar in the field of mental health from 2015 to 2019. The authors examined the retrieved articles for the gender gap in 1) the number of researchers. 2) the numbers of articles produced by men-only research teams vs. the research teams included women. 3) h-index. 4) foreign collaboration. 5) research design and themes. Results The authors identified 152 published articles in the field of mental health. Men researchers outnumbered women researchers (124 vs. 81). Men had statistically significant higher h-index compared to women (14.6 ± 1.4 vs 4.6 ± 0.9; p < 0.001). Research teams that included women had produced fewer articles compared to men-only groups (41.4 %), they also had less foreign collaborators (68 % vs. 91 %, p = 0.001). They were less involved in experimental research and more involved in observational research compared to male-only research groups (15.90 % vs. 38.6 % and 47.6 % vs. 25 % respectively; p = 0.034). In articles with women authors, women were the first authors in 50.8 % of the articles, and men were the senior authors in 79.4 % of them. Conclusion The study identifies gender gaps in some aspects of research productivity in Qatar. This data will provide a benchmark for future research in the field. Other Information Published in: Asian Journal of Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajp.2020.102347